2022
DOI: 10.3389/fvets.2022.863526
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Knowledge, and Perceptions Regarding Rabies Prevention Among Rural Communities in Masaka District, Central Uganda: A Qualitative Study

Abstract: Rabies is a zoonotic disease that is mainly transmitted to humans through dog bites. It remains a major public health threat in many Asian and African countries, including Uganda. The main objective of this study was to investigate awareness, knowledge, and perceptions of communities toward human and dog health related to rabies prevention, as well as dog management practices within Masaka district, central Uganda. Data collection involved nine key informant interviews (KIIs) and six focus group discussions (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This finding is in line with previous research on zoonotic disease in other contexts, which identified the high value of animals as a barrier to preventive health behaviors due to the economic impact of those behaviors [23][24][25][26][27]. Consistent with other literature, the current study found that the value individuals ascribe to their animals vary, including protecting the household, providing essential nourishment, and securing financial income [28]. These values may overlap and be somewhat fluid.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with previous research on zoonotic disease in other contexts, which identified the high value of animals as a barrier to preventive health behaviors due to the economic impact of those behaviors [23][24][25][26][27]. Consistent with other literature, the current study found that the value individuals ascribe to their animals vary, including protecting the household, providing essential nourishment, and securing financial income [28]. These values may overlap and be somewhat fluid.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, primary level of education, grazing, and fetching firewood in the GR were associated with rabies cases in households near to the GR. Primary level of education may only be associated with less awareness and knowledge about rabies (26). Grazing and fetching firewood in GR might be associated with rabies cases since these practices increase the possibility for wildlife-dog-human interaction (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, the vaccination of dogs is dependent on the socioeconomic status of the household or the locality. There is a need for rabies education and awareness initiatives including wound treatment (first aid) and PEP, because multiple studies have indicated a knowledge and awareness gap among individuals in LMICs [ 38 , 39 , 40 , 41 , 42 , 43 ]. Over 65% of Ghanaian respondents to a recent survey held the belief that rabies could be treated with a combination of concoctions, medical herbs, and the eating of offending dog meat [ 44 , 45 ].…”
Section: Socio-economic Factorsmentioning
confidence: 99%